Self-coherent detection in multicore fiber systems impaired by intercore crosstalk - Muga, N. J.; Alves, T. M. F.; Patel, R. K.; Alimi, I. A.; Pinto, A. N.; Cartaxo, A. V. T. (2023 23rd International Conference on Transparent Optical Networks (ICTON), 2023)
Space division multiplexing transmission, employing multicore fibers, as well as simplified self-coherent detection technologies have been intensively investigated in recent years to accommodate the demand for energy-efficient short-reach fiber-optic communication systems with extremely high capacity. Indeed, the conjugation of multicore fibers and simplified self-coherent receivers can be explored as a promising scheme to tackle the problems of capacity constraints in datacenter networks. This paper presents our recent investigations on the exploitation and optimization of novel self-coherent detection techniques, e.g. Kramers-Kronig and DC-Value methods. The performance assessment of weakly-coupled MCF-based systems that employ such new coherent detection receivers is presented.